The Construction and Measurement of an Online Learning Evaluation System Based on ACSI Mode - Han, Chunmei; Zhang, Yuzhuo; Yang, Hongji; Yu, Lu; Zhang, Lei (Learning Technologies and Systems, 2021)
Affected by the COVID-19 outbreak, most of Chinese universities have made the transition to online learning. Based on the American Customer Satisfaction Index (ACSI) Model, theoretical model of factors influencing online learning is constructed from the perspective of learners, which contained learner quality, instructor quality, technical system and educational system quality, perceived interaction and online perceived performance. Main findings include: (i) Learner quality has great predictive effect on online learning performance; (ii) Technical system and educational system quality is an important factor in predicting Online Learning effectiveness; and (iii) The predictiveness of perceived interaction and instructor quality is not strong.